Effect of Government Spending Policies on Education on Human Capital Accumulation and Economic Growth in the Middle East and North Africa (MENA) - Matyori, Emad Adnan (Journal of Economic, Administrative and Legal Sciences, 2021)
This study aims to estimates the effect of government spending on education and its policies on the accumulation of human capital and then economic growth, for this purpose, we use the econometric method, and employed the simultaneous equations model, for a sample of fourteen countries from the Middle East and North Africa (MENA) For the period (1980- 2019); The study concluded, in the first estimates stage of the model, that most of the government spending policies on education used in the study positively affect the accumulation of human capital, except, government spending policy on education at basic educational levels, which had a negative impact. And in the second estimates stage of the model, The study concluded, a positive impact of the accumulated human capital due to government spending on education and its policies on economic growth; Consequently, government spending policies on education positively affect economic growth through the channel of human capital accumulation, expressed in the composite index based on the Barrow- Lee database of average years of schooling for the working- age population, adjusted for the quality and return of education. The study made the following recommendations: interest to international education indicators data, as it is the basis for managing the educational system. Study more government spending policies on education to reveal its role in human capital accumulation and economic growth.: interest to human capital when formulating government policies, targeting its development, and increasing its contribution to GDP.
Keywords: Government spending policies on education; Human capital; Middle East and North Africa (MENA) countries; Economic growth